Rantai Nilai Tenun Muna di Desa Masalili, Madodo, Liangkobori, Bolo Kabupaten Muna - Mar’ath, Sitti Khafifatul; Budiani, Sri Rahayu (Jurusan Pendidikan Geografi Universitas Negeri Manado, 2024)
Muna weaving is a form of local wisdom in Muna Regency that has become the primary source of livelihood for the community. The purpose of this study is to determine the value chain and the actors involved in the value chain of Muna weaving. This study was conducted in four villages that serve as weaving centers in Muna Regency, namely Masalili Village, Madodo Village, Mabholu Village, and Liangkobori Village. Value chain analysis was used to identify the production process of Muna weaving, from the provision of raw materials to the final product reaching the hands of consumers. The results of the study show that the value chain of Muna weaving in Masalili Village differs from that of the other three villages due to variations in the use of raw materials and the distribution of weaving craftsmen as actors in the value chain. The entire production process is carried out in these four villages, and woven products are then distributed to consumers through three channels: purchasing through weaving entrepreneurs, purchasing directly from weaving craftsmen, or through distributors. Muna weaving is now being distributed and promoted abroad, demonstrating its great potential for further development.